Dimethylfumarate suppresses adipogenic differentiation in 3T3-L1 preadipocytes through inhibition of STAT3 activity. - Hyeon-Ji Kang; Hyun-Ae Seo; Younghoon Go; Chang Joo Oh; Nam Ho Jeoung; Keun-Gyu Park; In-Kyu Lee (PLoS ONE, 2013)
The excessive accumulation of adipocytes contributes to the development of obesity and obesity-related diseases. The interactions of several transcription factors, such as C/EBPβ, PPARγ, C/EBPα, Nrf2, and STAT3, are required for adipogenic differentiation. Dimethylfumarate (DMF), an immune modulator and antioxidant, may function as an inhibitor of STAT3 and an activator of Nrf2. This study examined whether DMF inhibits adipogenic differentiation of 3T3-L1 preadipocytes by inhibiting STAT3 or activating Nrf2. DMF suppressed 3T3-L1 preadipocyte differentiation to mature adipocytes in a dose-dependent manner as determined by Oil Red O staining. The mRNA and protein levels of adipogenic genes, including C/EBPβ, C/EBPα, PPARγ, SREBP-1c, FAS, and aP2, were significantly lower in DMF-treated 3T3-L1 preadipocytes. Suppression of adipogenic differentiation by DMF treatment resulted primarily from inhibition of the early stages of differentiation. DMF inhibits clonal expansion during adipogenic differentiation through induction of a G1 cell cycle arrest. Additionally, DMF regulates cell cycle-related proteins, such as p21, pRb, and cyclin D. DMF treatment markedly inhibited differentiation medium-induced STAT3 phosphorylation and inhibited STAT3 transcriptional activation of a reporter construct composed of four synthetic STAT3-response elements. Moreover, inhibition of endogenous Nrf2 activity using a dominant negative Nrf2 did not abolish the DMF-induced inhibition of adipogenic differentiation of 3T3-L1 preadipocytes. In summary, DMF is a negative regulator of adipogenic differentiation based on its regulation of adipogenic transcription factors and cell cycle proteins. This negative regulation by DMF is mediated by STAT3 inhibition, but is unlikely to involve Nrf2 activation.